Strike as The Last Resort In Dispute Settlement Between Workers and Employers - Arinto Nugroho (International Conference On Law, Business and Governance (ICon-LBG), 2013)
In order to maintain the continuity of the company's activities, harmonious relation between workers andemployers is a necessity. Unfortunately, the relationship does not always run as expected. In an attempt toresolve the dispute some cases showed that workers choose to use the Strike. Strike includes a workstoppage, sit-ins, slow down, and a ban on overtime. Strike is one of workers' rights as regulated in LawNumber 13 Year 2003. The problem that arises is the effects are complicated because it is associated withthe rotation of the economy in which the effects may be felt in the area of municipal level, provincialand/or Nation wide. Based on that background, the author wants to discuss about the use of Strike indispute settlement between workers and employer. The results of discussion shows that Strike is not thefirst choice of workers in resolving problems. Before conducting Strike the parties are required tonegotiate to reach an agreement beforehand. If these efforts fail then Strike comes up as an option. Underthese conditions, it can be said that the strike is the last resort in resolving disputes between workers andemployers